Studi Dampak Komunitas "Mari Menggambar" Terhadap Perkembangan Bakat Visual Bagi Remaja Di Kota Jakarta - Rafli Hidayah (VisArt: Jurnal Seni Rupa dan Design, 2025)
This research discusses the role of the community in increasing visual creativity among teenagers using a case study approach. This research aims to examine the impact of teenagers' participation in the "Let's Draw" community on the development of their visual talents. The method used is a mixed research method (qualitative and quantitative), which combines quantitative and qualitative data with a case study approach. This type of research uses surveys, interviews and observations on secondary and primary data to collect data from respondents and sources. The results of this research show that talent development among teenagers can be based on community activities such as workshops, joint discussions and weekly challenges. Apart from that, social interaction in the community has a positive psychological impact in the form of increased self-confidence and motivation to continue working. This research concludes that creative communities such as “Let's Draw” can be an effective platform to support the development of teenagers' visual talents. These findings provide recommendations for the formation of similar communities in other regions as a strategy to encourage creativity and artistic talent in the younger generation.